Microbial loop malfunctioning in the annual sea ice at Terra Nova Bay (Antarctica) - A. PUSCEDDU; A. DELL'ANNO; V. SAGGIOMO; S. COZZI; G. CATALANO; L. GUGLIELMO; VEZZULLI, LUIGI; FABIANO, MAURO (Polar Biology, 2009)
We investigated organic carbon quantity and biochemical composition, prokaryotic abundance, biomass and carbon production in the annual and platelet sea ice of Terra Nova Bay (Antarctica), as well as the downward fluxes of organic matter released by melting ice during early spring. Huge amounts of biopolymeric C accumulated in the bottom layer of the ice column concomitantly with the early spring increase in sympagic algal biomass. Such organic material, mostly accounted for by autotrophic biomass, was characterised by a high food quality and was rapidly exported to the sea bottom during sea ice melting. Prokaryote abundance (up to 1.3 9 109 cells L-1) and extracellular enzymatic activities (up to 24.3 lM h-1 for amino-peptidase activity) were extremely high, indicating high rates of organic C degradation in the bottom sea ice. Despite this, prokaryote C production values were very low (range 5–30 ng C L-1 h-1), suggesting that most of the degraded organic C was not channelled into prokaryote biomass. In the platelet ice, we found similar organic C concentrations, prokaryote abundance and biomass values and even higher extracellular enzymatic activities, but values of prokaryote C production (range 800– 4,200 ng C L-1 h-1) were up to three orders of magnitude higher than in the intact bottom sea ice. Additional field and laboratory experiments revealed that the dissolved organic material derived from algae accumulating in the bottom sea ice significantly reduced prokaryote C production, suggesting the presence of a potential allopathic control of sympagic algae on prokaryote growth.